Bite injuries at a level 1 trauma center in Germany - Monika Herten; Christina Polan; Steffen C Kraus; Heinz-Lothar Meyer; Bastian Mester; Gero Hilken; Marcel Dudda; Max Daniel Kauther; Manuel Burggraf (Trauma Surgery & Acute Care Open)
Background Bite injuries are a common occurrence and may result in significant morbidity. The aim of the study was to investigate bite injuries, their treatment, and consequences in the urban milieu of a European industrialized nation.Methods A retrospective, monocentric analysis was conducted on data of bite injuries during the study period from 2010 to 2020. Factors such as age, sex, vaccination status, injury pattern, injury location, the duration of treatment in outpatient, inpatient, or intensive care settings were investigated together with radiological, laboratory, and microbiological parameters, as well as the therapies employed.Results The majority of the included 442 patients were between the ages of 20 and 50, with a mean age of 37.2±18.4 years (0.7–91). The female sex was more frequently affected (59%). Most bite injuries were caused by dogs (49.9%), followed by cats (36.1%) and humans (9.8%) and were often caused by domestic animals (78%). The hand was the most common site of bites (n=251), followed by the forearms (n=75) and lower legs (n=43). In children under the age of 10, the head was the most common site of bites. In only 5% of patients, injuries extended to deeper structures. Wound infection was observed in 14.7% of the bite wounds. The mean number of treatment days for patients with infected bite wounds was significantly higher than that for patients with non-infected wounds, regardless of whether they were outpatients, inpatients, or intensive care patients (p=0.001, p<0.001, and p=0.003, respectively).Conclusions In accordance with the severity of the injury, a prompt examination, imaging, laboratory diagnostics, and individualized therapy are required. The implementation of an early therapeutic regimen comprising debridement and irrigation, calculated antibiotic therapy, and immobilization can effectively mitigate the risk of developing a fulminant wound infection. Similarly, bite wounds caused by exotic species are to be treated with haste and precision.Level of evidence Level III study: non-experimental descriptive studies.